Soil organic carbon sequestration mediated by plant–microbe interactions after compost application - Shelby C. McClelland; Meagan E. Schipanski (Ecosphere)
Abstract Organic amendments like compost can enhance soil health and climate change mitigation in managed grassland ecosystems. We previously demonstrated in a northern Colorado cool‐season pasture that infrequent compost applications support net soil organic carbon sequestration. Here, we examined plant and soil biota responses over three growing seasons to better understand how plant–soil feedbacks support net sequestration under compost. Compost doubled soil P and increased soil K by one‐third, but slightly decreased soil pH in the top 10 cm of soil. Differences in plant production and plant community composition were immediate after application and sustained over the experimental period while soil biota were slower to respond. A path analysis (χ2 = 14.0, p = 0.23) suggests that the plant effect on soil organic carbon sequestration (R2 = 0.67) was fully mediated by the soil microbial community, especially bacteria. Our work supports the importance of microbially derived inputs for building soil organic matter in grasslands receiving organic amendments.